The Ideological Origins of Nazi Imperialism. - Smith, Woodruff D. (Oxford University Press, 1989)
The author argues that the imperialist ideology and policies adopted by the Nazis must be seen as the result of a complex evolution of imperialist thinking in Germany, having its roots in the 19th century.